Microbial ecology of aerial plant surfaces - Bailey, M. J.; Bailey, M. J.; Lilley, A. K.; Lilley, A. K.; Spencer-Phillips, P. T. N.; Spencer-Phillips, P. T. N.; Timms-Wilson, T. M.; Timms-Wilson, T. M. (Wallingford :CABI, 2006)
This book focuses on the ecology of the microbiology of the surfaces of above-ground, aerial portion of vascular plants (including stem, leaves, fruits and flowers), collectively known as the phylloplane. It is divided into 6 sections, highlighting both the value of this highly diverse habitat to research in microbiology and the importance of this research to plant health and ecosystem functions. Section I concerns the biodiversity and population genetics of phyllosphere communities. Section II concerns the spatial distribution and biofilm structures of microbes on the phylloplane. Section III concerns biological control and pathogenicity. Section IV describes gene expression and phyllosphere genomics. Section V focuses on leaf colonization and dispersal. Section VI deals with aerobiology and plant surface microbiology.
Keywords: FF610 - Viral, Bacterial and Fungal Diseases of Plants, (New March 2000); HH100 - Biological Control; PP700 - Biological Resources (General); ZZ333 - Microbial Ecology, (New March 2000); ZZ360 - Molecular Biology and Molecular Genetics, (Discontinued March 2000, Reinstated and Revised June 2002); ZZ395 - Genetics and Molecular Biology of Microorganisms, (New March 2000)